2000
DOI: 10.1097/00003072-200010000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hemangioma

Abstract: A 53-year-old man was found serendipitously to have increased blood-pool uptake in the right lobe of the thyroid during a radionuclide ventriculography study for left ventricular function. Primary thyroid hemangioma is a rare condition, with only two cases reported in the literature. Secondary hemangioma may occur as a result of fine-needle aspiration. This technique may cause hematoma formation, which generally resolves normally, but on rare occasions it can lead to cavernous hemangioma formation. In patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…In most cases, thyroid hemangioma is associated with FNA biopsy or trauma, which may be regarded as abnormal vascular proliferation following hematoma organization, or as a secondary lesion that resulted from the vascular changes during the development of nodular goiter. [ 7 ] Kumar et al [ 6 ] suggested that primary thyroid hemangioma originated from the incapability of the canal formation in the angioblastic mesenchyma. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, thyroid hemangioma is associated with FNA biopsy or trauma, which may be regarded as abnormal vascular proliferation following hematoma organization, or as a secondary lesion that resulted from the vascular changes during the development of nodular goiter. [ 7 ] Kumar et al [ 6 ] suggested that primary thyroid hemangioma originated from the incapability of the canal formation in the angioblastic mesenchyma. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 5 ] Primary thyroid hemangiomas are considered as a developmental anomaly that is associated with an inability of angioblastic mesenchyma. [ 6 ] Generally, no prominent clinical manifestations but a cervical mass can be found in the patient with thyroid hemangioma. In addition, the preoperative diagnosis is difficult to be made because no distinctive signs observed by ultrasonography or computed tomography (CT) scans.…”
Section: Introductionmentioning
confidence: 99%
“…Vitiligo is one of the most prevalent acquired pigmentation conditions 1 2. It poses a significant psychosocial burden1 and can be psychologically traumatic, especially in African and Asian people 2…”
Section: Discussionmentioning
confidence: 99%
“…It poses a significant psychosocial burden1 and can be psychologically traumatic, especially in African and Asian people 2…”
Section: Discussionmentioning
confidence: 99%
“…Hemangioma Primary thyroid hemangioma is a rare condition, with less than five cases reported in the literature so far [32][33][34][35]. Secondary hemangioma may occur as a result of FNA, connected with the organization of a thyroid hematoma after the puncture, which generally resolves normally, but on rare occasions can lead to cavernous hemangioma formation.…”
Section: Other Entitiesmentioning
confidence: 99%